[PP.01.07] CARDIOVASCULAR RISK FACTORS IN URBAN VERSUS RURAL AREA OF ORIGIN IN THE EASTERN EUROPE HYPERTENSIVE PATIENTS. (September 2017) - Varga, A.; Tilea, I.; Tatar, C.M.; Morar, S.; Bocicor, A.E.
Abstract : Objective: Study of the cardiovascular (CV) risk factors in hypertensive patients, urban versus rural (U/R) area of origin, in primary care. Design and method: We analyzed and compared the data of 525 hypertensive patients divided in active group 485 (92.4%), deceased group 31 (5.9%) and 1.7% lost to follow-up group at the end of the study Results: Mean age 62.06 ± 12.303 y.o, no significant differences (p = 0.28) among the gender distribution or by the origin (p = 0.09) in 21.3% smokers, 42.28% patients with hypercholesterolemia, and 35.23% with hypertriglyceridemia. Risk factors: obesity, smoking/non-smoking status, hypercholesterolemia, hypertriglyceridemia, mixed dyslipidemia and diabetes, were analyzed, with no statistical significance (p > 0.05) for the prevalence of these risk factors in urban versus rural area, between the active and deceased group. In smoker versus non-smoker, we identified a p = 0.03 for active hypertensive patients in the urban area. Obesity was associated with statistically significant (p = 0.02) CV risk stratification of high and very high risk. In the same two analyzed groups, the presence of different concomitant CV risk factors was not statistically significant (p = 0.17); 50.7% of patients had at least 2 concomitant risk factors associated with hypertension. In the active hypertensive group, 30% of urban area, presents one CV risk factor versus 41.2% in rural area, but in the urban hypertensive patients there is a progressive increase in the percentage of patients presenting a higher number of different concomitant risk factors associated with hypertension, compared to rural areas. 52.1% of active hypertensive patients in urban area have more than two CV risk factors concurrently with hypertension. In rural area, for patients in the active group, the association of least three different CV risk factors concurrently with hypertension was found in 17.7% patients. Conclusions: Dyslipidemia in hypertensive patients, represent a modifiable risk factor to reinforce the control strategies for, irrespective of urban or rural area. It is emphasized the importance for an individual cardiovascular risk assessment for each hypertensive patient.